Impacts of experimental drought on community structure and floristic composition of tree saplings in a lowland tropical rainforest in Eastern Amazonia - Ferreira, Leandro Valle; Cunha, Denise de Andrade; Parolin, Pia; Costa, Antônio Carlos Lôla da (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
In order to test the effect of the lower availability of water for vegetation in a tropical Amazonian forest, a long-term research project was created in 2001 called Projeto Seca Floresta (ESECAFLOR). The main objective of the project is to determine how a significant reduction of the available water in the soil, in the long term, can affect the biota. The ESECAFLOR consists of two 1-hectare plots, the experimental plot is covered with 6,000 plastic panels reducing precipitation by 50%. The objective of this work is to compare the floristic and plant structure (< 2 meters high) between the experimental and control of ESECAFLOR plots. There was a significant reduction in species richness and diversity, plant density and height, and a significant change in species composition between experimental plot compared to control. The plant community clearly responded to the reduction of soil moisture in the experimental plot, corroborating the results of some climate models that say rainfall reduction in the Amazon will negatively affect the plant community.
Keywords: Drought effects; Soil water availability; Tree sapling community; Amazon rainforest